Drug policing in four Danish police districts. (3rd July 2016) - Houborg, Esben; Kammersgaard, Tobias; Mulbjerg Pedersen, Michael
Abstract: Results from a study of zero-tolerance drug policy in Denmark are presented. Database research shows that an increasing number of Danes are criminalized for possession of illicit drugs and that particular characteristics of offenders increase the chance of being criminalized. Qualitative case studies show ambiguous results. Criminal records do not indicate that particular people are singled out. Interviews with police officers indicate that appearance of persons and non-offending behavior can play a role in suspicion formation and legal action. The ambiguity of the results can be seen as a reflection of the differences in the data where some of the grounds for police intervention may be seen by police officers as not appropriate for official recording. To resolve these issues and provide better knowledge regarding drug policing in Denmark, further research is needed.